2019
DOI: 10.1038/s41598-019-50088-1
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the chromatin remodeler HELLS is mediated by YAP1 in Sonic Hedgehog Medulloblastoma

Abstract: Medulloblastoma is a malignant pediatric tumor that arises from neural progenitors in the cerebellum. Despite a five-year survival rate of ~70%, nearly all patients incur adverse side effects from current treatment strategies that drastically impact quality of life. Roughly one-third of medulloblastoma are driven by aberrant activation of the Sonic Hedgehog (SHH) signaling pathway. However, the scarcity of genetic mutations in medulloblastoma has led to investigation of other mechanisms contributing to cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Seven of the 13 genes were highly expressed in testis, but low in other tissues. None of the signature genes except TERT was cataloged by the expert-curated Cancer Gene Census 44 (as of July 2020), although LIN9 and HELLS were recently implicated in cancer 45,46 . Mutations in HELLS, a gene encoding a lymphoidspecific helicase, cause the centromeric instability and facial anomalies (ICF) syndrome, a genetic disorder associated with short telomeres 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the 13 genes were highly expressed in testis, but low in other tissues. None of the signature genes except TERT was cataloged by the expert-curated Cancer Gene Census 44 (as of July 2020), although LIN9 and HELLS were recently implicated in cancer 45,46 . Mutations in HELLS, a gene encoding a lymphoidspecific helicase, cause the centromeric instability and facial anomalies (ICF) syndrome, a genetic disorder associated with short telomeres 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal epigenetic regulation related to histone modifications have been recently reported in SHH MB (Robinson et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In medulloblastoma, YAP1 is significantly amplified and upregulated in SHH-activated subtypes and mediates SHH-driven NPC proliferation ( Fernandez et al, 2009 ). More recently, studies have shown that YAP1 expression leads to upregulation of chromatin remodeler helicase, lymphoid specific (HELLS) in SHH-activated medulloblastoma and is activated downstream of SHH pathway activation through SMO, a positive transducer of SHH signaling ( Robinson et al, 2019 ).…”
Section: Early Embryogenic Pathways and Morphogensmentioning
confidence: 99%